2022
DOI: 10.3390/vaccines10111897
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Willingness to Vaccinate Children with Pneumococcal Vaccines and to Pay in a Low-Resource Setting in China: A Cross-Sectional Study

Abstract: To determine the vaccine hesitancy of pneumococcal conjugate vaccines (PCVs) in a low-resource setting in China and to identify associated factors, a face-to-face questionnaire survey was conducted in the city of Guilin, China, from December 2021 to March 2022, which comprised sociodemographic information, attitudes toward vaccines and pneumonia, and PCV13 vaccination willingness and willingness to pay (WTP). Stepwise logistic regression and Tobit regression models were fitted to identify factors associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The underlying reasons for their hesitancy need to be investigated further because of their essential role in vaccination promotion. 34 , 35 In another survey conducted at the same time as this one (not yet published), we found that the primary barrier was fear of infection during the vaccination process. It implies that measures that can reduce SARS-CoV-2 infection risk during vaccination (e.g.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The underlying reasons for their hesitancy need to be investigated further because of their essential role in vaccination promotion. 34 , 35 In another survey conducted at the same time as this one (not yet published), we found that the primary barrier was fear of infection during the vaccination process. It implies that measures that can reduce SARS-CoV-2 infection risk during vaccination (e.g.…”
Section: Discussionmentioning
confidence: 60%
“…For “sociodemographic information,” older age, male sex, and high education level were positively associated with vaccine acceptability, which is consistent with other studies. 33 , 34 Besides, healthcare workers showed lower vaccine acceptability than non-healthcare workers for both recommendation willingness and preference for intranasal spray. The underlying reasons for their hesitancy need to be investigated further because of their essential role in vaccination promotion.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies about the acceptance and WTP of non-immunization vaccines have been conducted in China. These studies concern individual vaccines such as HPV vaccine, 21 , 29 pneumococcal vaccine, 30 COVID-19 vaccines, influenza vaccines. 29 , 31 , 32 To our knowledge, this is the first time that parental WTP for hexavalent vaccine has been investigated in China’s mainland.…”
Section: Discussionmentioning
confidence: 99%
“…In China, the coverage rate varies greatly by region and is especially limited in low-resource settings. Cost, insufficient vaccine knowledge and not being included in the National Immunisation Programme were found to be the major reasons for vaccine refusal and hesitancy [ 127 ]. Health disparities between low- and high-income provinces persist and remain an important target of China's health reform [ 128 ].…”
Section: The Chinese Situationmentioning
confidence: 99%